Microvessel density in different grades of oral squamous cell carcinoma and its relationship with keratin pearl - Zeng, Zhou Tan; Mohammad Zakir Hossain; MD Shahidul Ahsan; Yew, Choy Chew; Swe, Swe Win; Suan, Phaik Khoo (Universiti Kebangsaan Malaysia, 2016)
Angiogenesis has an important role in the invasion, metastasis and growth of tumors. Increased microvessel density (MVD) has been described in oral squamous cell carcinoma (OSCC) compared to oral dysplasia and normal oral tissue. A morphometric study was designed to evaluate the MVD and to evaluate the presence of any association between MVD and keratin pearl in the three histopathological grades of OSCC (as defined in Bryne’s grading system). Forty-five samples of OSCC were graded into well differentiated (WDSCC), moderately differentiated (MDSCC) and poorly-differentiated (PDSCC) oral squamous cell carcinoma. Morphometric analysis showed that MVD was significantly lower in WDSCC compared to MDSCC (p<0.001) and PDSCC (p<0.001). The density in MDSCC was significant lower than PDSCC. The keratin pearl count was significantly higher in WDSCC compared to MDSCC (p<0.001) and PDSCC (p<0.001). Between MDSCC and PDSCC, the keratin pearl count was significantly higher for MDSCC (p=0.001). Pearson correlation test showed a significant negative correlation between keratin pearl and MVD (r=-0.805, p<0.001). The findings suggested that vascularity in OSCC is associated with its cellular differentiation and also associated with keratin pearl formation.